Performance investigation of vapor compression cycle with a variable speed compressor and refrigerant injection / Ahmed J. Hamad...[et al.] - J. Hamad, Ahmed; N. Khalifa, Abdul Hadi; Z. Khalaf, Doaa (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2019)
The performance of vapor compression refrigeration system with controllable speed compressor and vapor and liquid refrigerant injection techniques is experimentally investigated. For this purpose, a 5-tons (17.6 kW) split air conditioner unit charged with R-22 refrigerant was modified and equipped with, frequency inverter, secondary capillary tube, and liquid pressure amplification pump (LPA). Vapor refrigerant was injected into the accumulator with three injection mass ratios 2, 3, and 4%. LPA pump was used to inject liquid refrigerant from the condenser outlet to the discharge line with injection mass ratios 0.5%, 1.5%, and 2%. The compressor speed was controlled by frequency inverter, where the range of the frequency used was from 35 to 60 Hz with 5 Hz step. The results showed that the coefficient of performance (COP) of the modified system using vapor injection technique was improved by 11.26% compared to the conventional system, and the suction temperature reduced from 10.3 to -0.1°C with 3% vapor injection ratio. The best enhancement in COP was 9.9% for the 0.5% liquid injection ratio. Reduction of the compressor speed leads to improve the COP by 18% and reduces the compressor power by 36.4% at frequency 35Hz. Using the vapor injection with variable speed compressor improved the COP of the modified system by 75% at 35 Hz and 2% injection mass ratio.